2011
DOI: 10.1080/03630242.2011.574791
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Psychological Stress to Pregnancy Outcome Among Women Undergoing In-Vitro Fertilization and Intracytoplasmic Sperm Injection

Abstract: A considerable literature has been accumulated regarding the relation of psychological factors to in-vitro fertilization outcome. However, study findings have been inconsistent, and the association between psychological stress and in-vitro fertilization outcomes is still unclear. The aim of the authors in this study was to examine the relation of infertility-related stress, anxiety, and depressive symptoms to in-vitro fertilization outcome. The sample consisted of 160 women with fertility problems undergoing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 47 publications
1
48
0
1
Order By: Relevance
“…The Fertility Problem Inventory (FPI) was developed in 1999 as a specific measure of infertility-related stress in males and females [54] and has been utilised in a number of interventional studies [35, 37, 41, 42]. The FPI was developed through a qualitative literature review to inform the underlying concepts [54].…”
Section: Resultsmentioning
confidence: 99%
“…The Fertility Problem Inventory (FPI) was developed in 1999 as a specific measure of infertility-related stress in males and females [54] and has been utilised in a number of interventional studies [35, 37, 41, 42]. The FPI was developed through a qualitative literature review to inform the underlying concepts [54].…”
Section: Resultsmentioning
confidence: 99%
“…14 Gourounti et al, argue that the increasing level of anxiety and infertility distress during treatment has a negative influence on pregnancy rates. 15 It has been reported that anxiety increases in the infertility treatment process 5 and decreases with the use of effective coping methods. 16 According to Pasch, the most important point to be taken into account to decrease anxiety in the infertility treatment process and in case of failure of the treatment is not only to prepare patients for the infertility treatment process and for the possible failure of the treatment, but also to help them cope with this effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers and clinicians have shown that psychological factors might reduce the chances of achieving pregnancy with IVF [35]. Previous studies have revealed a possible association between stress and reproductive outcomes.…”
Section: Introductionmentioning
confidence: 99%